Pengaruh Model Pembelajaran Berbasis Masalah Berbantuan Media Phet Terhadap Hasil Belajar Fisika Siswa Kelas X SMAN 1 Gunungsari Tahun Pelajaran 2015/2016 - Tantawi Jauhari; Hikmawati Hikmawati; Wahyudi Wahyudi (Department of Physics Education, Universitas Mataram, 2016)
This research aims to find out the effect of problem based learning model with PhET media on the studentÃ¢â¬â¢s results of physics learning of Xthgrade SMAN 1 Gunungsari in academic year 2015/2016. This research is a quasi experiment with nonequivalent control group design. The population of this research is all of Xthgrade student which amounted to 333 students, and the sample is the student at X.6 which amounted to 34 student as experiment class and student at X.7 which amounted to 35 student as control class. The sample was got by using the cluster purposive sample. The result of pre-test showed that the average value of experiment class is 34,35, while the control class around 43,66. The result of post-test showed that the average value of experiment class is 70,24, while the control class around 57,60. The study tested the hypothesis with t-test polled varians. Based on the result of hypothesis testing, tcount = 4,93 and ttable = 1,99 with significance level of 5% and tcount>ttable, then Ho rejected and Ha accepted. So can be concluded that there is an effect of problem based learning model with PhET media on the studentÃ¢â¬â¢s results of physics learning of Xthgrade SMAN 1 Gunungsari in academic year 2015/2016.